THE DEVELOPMENT AND QUALITY OF THE ENGLISH HOUSEKEEPING MATERIAL DEVELOPED AT SMKN 1 AMLAPURA - Ni Nyoman Arie Millenia Ratri; Nyoman Karina Wedhanti; Gede Mahendrayana (JELLT (Journal of English Language and Language Teaching), 2023)
Abstract: Schools must prepare students well in the learning activity, especially in VHS or vocational high schools. The instructional materials used must be suitable and specific to each lesson. However, there are teaching materials that are still of low quality and are not in accordance with the needs of students. Therefore, the purpose of this study is to determine the quality of English housekeeping materials developed for class XI students at SMK Negeri 1 Amlapura. The subject of this research was one class consisting of 38 of eleventh-grade students of hospitality major and one housekeeping teacher at SMK Negeri 1 Amlapura. In this study, the researcher used one instrument namely a checklist for expert judges in collecting the data. This research used (D&D) Design and Development as the research method and used quantitative data analysis techniques. The result shows that the product developed consists of two units namely (1) equipment selection and arrangement and (2) area cleaning. The score from the expert judges’ checklist was 100 and 97. After conducted the data analysis process, the percentage of the product validity level of two expert judges was 4 and 3,88 which classified as very good. The conclusion obtained in this study is the product developed for eleventh-grade students at SMK Negeri 1 Amlapura categories as very good and acceptable to use for students and also teachers.